Risk Factors Associated with Outcomes of Continuous Ambulatory Peritoneal Dialysis Survival: A Single-Center Study in A General Hospital - Makruasi, Supap; Khuancharee, Kitsarawut; Makruasi, Nisa (Asian Medical Journal and Alternative Medicine, 2021)
Introduction: Continuous ambulatory peritoneal dialysis (CAPD) has improved survival for renal replacement therapy in patients with end-stage renal disease (ESRD) in Thai patients. The benefit of CAPD in ESRD patients has been demonstrated in medical and quality of life. Nevertheless, the data of risk factors associated with CAPD mortality is dismal. Thus, this study aims to identify the factors associated with mortality of ESRD patients treated by CAPD modality. Methods: A retrospective cohort study enrolled ESRD patients who had received CAPD in a general hospital in Nakhon Nayok, Thailand. Medical records including clinical characteristics, laboratory, and mortality outcomes were reviewed and analyzed, respectively. A Cox proportional hazard regression method was performed to evaluate the risk factors associated with mortality outcomes. Overall survival (OS) was calculated using the Kaplan-Meier method. Results: Two hundred and twenty-eight ESRD patients receiving CAPD between 2012 and 2019 were enrolled in the study. The median OS was 2.5 years (95%CI: 1.8 - 3.5). Multivariate analysis showed patients with older age (≥ 65 years), diabetes mellitus, and low serum albumin (< 2.5 g/dL) associated with mortality outcomes. Conclusions: Elderly patients, diabetes mellitus, and low serum albumin have been risked factors for overall mortality in CAPD patients.